2021
DOI: 10.9734/mrji/2021/v31i330307
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba gingivalis and Trichomonas tenax in Periodontal Disease

Abstract: This review is aimed at elucidating the role of Entamoeba gingivalis and Trichomonas tenax in the aetiology of periodontal disease. Periodontal disease results from localised inflammation of the periodontium due to plaque accumulation and if left untreated can lead to loss of teeth. Although dental plaque is composed mainly of bacteria, Entamoeba gingivalis and Trichomonas tenax, both of which are protozoan parasites have been found in plaque and implicated in periodontal disease. E. gingivalis is an amoeba as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
0
0
Order By: Relevance
“…and 52.4% in (41-60 Y.). This is in agreement with previous studies that the prevalence of these protozoa increases with age as 35% (<40 years) to reach 85% in older subjects (>60Y) [22]. A study performed on diabetic patients concluded that prevalence increases with age with maximum prevalence in (61 -70 age group) [7].…”
Section: Discussionsupporting
confidence: 92%
“…and 52.4% in (41-60 Y.). This is in agreement with previous studies that the prevalence of these protozoa increases with age as 35% (<40 years) to reach 85% in older subjects (>60Y) [22]. A study performed on diabetic patients concluded that prevalence increases with age with maximum prevalence in (61 -70 age group) [7].…”
Section: Discussionsupporting
confidence: 92%
“…[ 9 ] The other original article deals with association and role in pathogenesis of two oral commensal protozoa in peri-odontal disease. [ 10 ] In the Dispatch section, there is one case report of appendicitis caused by Entamoeba ,[ 11 ] and another of Hydatid disease in the infraspinatus muscle. [ 12 ] Subcutaneous dirofilariasis,[ 13 ] a series of three cases of hepatic visceral larva migrans caused by Toxocara spp,[ 14 ] and finding of four protozoa in the stool of a patient[ 15 ] constitutes the other dispatch articles.…”
mentioning
confidence: 99%